TAFSIR AYAT-AYAT SOSIAL KEMASYARAKATAN DALAM AL-QURAN - Zabidi, Ahmad (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
The purpose of this research is to describe the interpretation of social verses in the Koran. The method used in this research is a qualitative method with the type of research library research (literature review), while the technical data analysis uses content analysis (content analysis). The results of this study indicate that the foundation of legal and social justice is faith, which is essentially stated in the two sentences of the creed. Deliberation has deep potential in the life of Islamic society which is not just a political system of government. Deliberation is the basic character of the whole society. All issues are based on deliberation. Ukhuwah is defined as